ASSESSING THE QUALITY OF THE LOCAL DEVELOPMENT STRATEGIES IN ROMANIA, EVIDENCE FROM 2014-2020 PROGRAMMING PERIOD - Alexandru OLAR; Ionel-Mugurel JITEA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The LEADER Program has become an important part of the EU Rural Development policy since 1990. The program aims to offer solutions that are adapted to the needs of the rural communities and territories. The objective of the present work is to assess how the Local Development Strategies (LDS), created by the Romanian Local Action Groups (LAGs) between 2014 and 2020, respond to those needs. The study was conducted in the Nord-West Development Region of Romania, using quantitative and qualitative data from 31 LAGs. Two main types of data were used. The first set contains key rural development indicators - as defined and used by EU - and information from their own SWOT analysis, and are used to find out the needs, while the second set contains the objectives assumed by LAGs. A principal Component Analysis was performed in order to identify the factors that determine the quality of the Local Development Strategies. The results show that the Local Action Groups have not used a unitary methodology for selecting the indicators. More often than not, they chose to use irrelevant indicators that were not covered in official data and in the established methodologies of the European Union. A positive correlation was identified between the local characteristics (territory and population) and the budget allocation. However the strategies fail to address and respond to the needs and opportunities from the priorities that deal with knowledge transfer and innovation (P1) and the shift towards a low carbon and climate resilient economy (P5).